Exploring the views of university students on institutions. A validation exercise through triangulation of statistical techniques - Varela, Sebastián; Barandiarán, Santiago (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2016)
Studies on institutional confidence of young people in the region are scarce, and rarely offer an explanatory analysis of the differences found in the levels of confidence in major social institutions. Based on a review of relevant literature, this study provides an analysis of institutional confidence patterns through multivariate statistical techniques, namely principal components analysis, classification and regression trees and factorial analysis of variance. The results show that the studied population makes clear distinctions between public and private institutions, both in the sense that it grants greater confidence to the first, and also the fact that explanatory factors of confidence in public institutions are different from those explaining confidence in private institutions.